Instalasi Air Bersih dan Air Kotor pada Rusunawa Telaga Gorontalo - Nento, Ilyas Rivaldi U.; Husnan, Rawiyah; Alitu, Aryati (Jurnal Teknologi Berkelanjutan, 2024)
Clean water is water that is used for daily purposes and can be consumed, while dirty water is wastewater resulting from human activities and cannot be consumed. The existence of clean water and dirty water distribution is needed for the benefit of the residents. This study aims to analyze the need for clean water and dirty water in the Telaga Gorontalo Flat Building in accordance with the calculations carried out and the installation of clean water and dirty water.. The results were analyzed using the survey method and looking at the available siteplan. There are 42 housing units with type 36 which are divided into 3 floors with a total unit area of 1,512 m2, has a total occupancy of 168 people, with a water demand value per person (Qr) of 100 liters / person / day. The analysis shows that the clean water demand of Telaga Gorontalo Flat is 20.16 m3/day, the waste water generated is 13.44 m3/day and the volume of septic tank generated is 35.12 m3. For the installation of clean water pipes, some pipes are not in accordance with the results of calculations such as flush toilet pipes and ablution urinal pipes while for the installation of dirty water pipes and waste water installed are in accordance with the calculation results.